A biblioteca escolar no processo de escolarização da leitura no contexto do Movimento Escola Nova: 1920-1940 - Marcus Vinicius Rodrigues Martins (2013)
This dissertation aims to investigate the place of the school library in the period 1920-1940 in Minas Gerais . Methodologically it was used, among the qualitative methods, historical analysis and techniques of documentary and bibliographic research. It was included in the documentation reviewed: laws, enactments , letters , reports of school board inspection grouped in books and codices within the chronological cut mentioned above . It was made an analysis of the journal articles that had the themes "Library or "reading books" . We attempted to contextualize the temporal arc from 1920 to 1940, in order to understand the importance for the formation of the Brazilian state, especially the installation of the Republic, also the urban and educational reforms. We identified the statements that built a school model that conformed modern, republican and civilizing ideas and changed the times , spaces , school practices and methods in the light of educational theories arising from the movement " Progressive Education" . We analyzed the ideal pedagogical renovator from their European and American constitution and its reverberations in Brazil . We attempted, from the regionalist point of view , demonstrate how was Minas Gerais' reaction facing innovative ideas and reports the experience of the Institute João Pinheiro . We situated the educational reform of Francisco Campos and Catholic progressive education, hallmarks of Minas Gerais in face of Progressive Education movement. We identified the discourses of Fernando de Azevedo Teixeira, Cecilia Meireles , Armanda Álvaro Alberto Lourenço Filho and others who reframed books , reading and libraries . We analyzed the statements that have reshaped the following aspects: the modes of reading, the setting of the book , their presence in schools and the establishment of children's literature and a publishing market . We pointed up the discourses of educators on the school library, its importance and presence in the educational context and showed up at the Progressive Education School experiences of São Paulo and Rio de Janeiro libraries. We mapped the data on the existence of school libraries over the years 1933 to 1943 in the Brazilian states, which allow us to infer that the increase in the number of libraries is linked to educational reforms and to discourses of educational reformers. We made the contextualization and analysis of mapped sources to produce the following results: the configuration and structuring dedicated to the school library spaces, the importance of the speeches of politicians and educators from the state of Minas Gerais , the presence of these spaces in plants of school groups , standards in disciplinary environment, the matter of the organization of school libraries in terms of materials acquisition, school projects , cataloging and lending policies . We analyzed the requirement of the books that would compose the collections and a whole discursive field that would agree to moral and social values. We also examined the role and activities indicated by the educators to librarians or Library Teachers." It was concluded that there was a repositioning of the library place and that it has complied in their practices , time, space and collections with the Republican imagery and modernist, industrial rise , the hygienist and the ideal of the "Progressive Education".